Obywatelstwo i prawa społeczne Unii Europejskiej w dobie kryzysu gospodarczo-politycznego - Kornobis-Romanowska, Dagmara (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Citizenship, social rights and crisis are the three phrases that appear with the legal issue presented in this paper. They are also one of the most pressing social, legal, and economic problems in the European Union, valid not only today, and inherent for European integration throughout all the years of its existence.Today, it may be concluded that the process of creating a common market is coming to an end, while the institution of Union citizenship is still in a state of constant change. The political and economic situation in Europe has led to a narrowing of the rights of EU citizens, from market citizenship, via social citizenship, to the reliance on the doctrine of the “essence of rights” only in very special and exceptional circumstances. Therefore, despite the fact that EU citizenship finds its basis in EU law, it results in practice in the status of the individual in the given host country rather than in its formal position in the EU. However today, more than ever, citizenship of the EU consists of active participation in the community, since the European community is real.
Keywords: European Union; citizenship; social rights; economic and political crisis